(untitled) (The Research of Medical Science Review, 2025)
Introduction: One of the most common eye conditions for which individuals seek medical care is Dry eye disease (DED) also known as keratoconjunctivitis sicca, dry eye syndrome, or dysfunctional tear syndrome. The anti inflammatory effect of IPL was compared with conventional therapy including topical Tobra plus Dexa along with Warm compresses by the patient Dry eye associated with MGD were investigated in this study. Materials and Procedures: Patients Pstients having Dry eye disease (DED) and meibomian gland dysfunction (MGD) were split into two groups of 54 patients, each with 27 members. IPL was used to treat Group A, whereas a warm compress and tobramycin/dexamethasone were used for Group B for 1 month. TBUT and OSDI were measured before and one month after treatment. Results: At one month following therapy, both Group A and Group B showed improvements in OSDI and TBUT as compared to baseline, which were statistically significant (P<0.05). Group A's TBUT was improved more than Group B's at one month (P=0.0001) and so was OSDI (P<0.05). Conclusion: Our study concluded that IPL treatment was superior to tobramycin/dexamethasone plus warm compress treatment for improving TBUT and OSDI in patients with DED associated MGD over a one-month treatment period.